Introduction to Mechanics of Materials, An. - Gupta, Vijay (Alpha Science International, 2013)
AN INTRODUCTION TO MECHANICS OF MATERIALS attempts to deal with the subject as an engineering science with a clear elaboration of the central scheme of dealing with this subject, namely, delinking the geometry aspects of the subject from the materials aspects. This is achieved by using explicitly the three-step scheme of macro (forces) to micro (stresses) conversion, transforming at the micro level (from stresses to strains), and then converting back to the macro level (deformations), or vice versa. Another aspect which has been emphasized considerably is the construction of idealized models o.